A case of successful maintained pregnancy after neoadjuvant chemotherapy plus radical surgery for stage IB3 cervical cancer diagnosed at 13 weeks - Ying Guo; Dandan Zhang; Yuhong Li; Yudong Wang (BMC, 2020)
Abstract Background Cervical cancer during pregnancy is rare. The management for stage IB3 during pregnancy remains unclear and challenging. We report a successful preserved pregnancy in a stage IB3 patient who was treated with neoadjuvant chemotherapy (NACT) plus radical surgery. Case presentation A 36-year-old pregnant woman was diagnosed with a 5-cm-diameter stage IB3 squamous cell carcinoma of the uterine cervix at 13 gestational weeks. The patient received 5 courses of systemic chemotherapy with carboplatin and paclitaxel every 3 weeks, followed by caesarean section and radical hysterectomy. Both the mother and infant are in good general condition. Conclusion This case suggests that NACT plus radical surgery could be one method to maintain pregnancy in stage IB3 cervical cancer diagnosed as early as 13 gestational weeks.